Sectoral Differences in Financial Performance Before and After IPO: Evidence from the Indonesia Stock Exchange - A. A. Rai Niti Darmika Sukawati; I Made Ryan Ananta Putra; Kedisan, A.A. Vidyaswari (E-Jurnal Akuntansi, 2025)
This study examines sectoral differences in financial performance changes before and after Initial Public Offerings (IPOs) on the Indonesia Stock Exchange during the 2020–2023 period. The research population includes all firms conducting IPOs in the observed period, with 235 companies selected using purposive sampling based on data availability. Financial performance changes are measured using the Current Ratio (CR), Total Assets Turnover (TATO), Debt to Equity Ratio (DER), and Return on Equity (ROE). Sectoral comparisons are conducted using the Kruskal–Wallis non-parametric test due to non-normal data distribution. Descriptive results indicate that liquidity (CR) generally increases after IPOs, while efficiency (TATO), leverage (DER), and profitability (ROE) tend to decline. However, the Kruskal–Wallis results show no statistically significant differences in these changes across sectors. Overall, post-IPO financial adjustments in the Indonesian capital market exhibit relatively homogeneous patterns across industries during the observed period.